A study on the impact of sustainable management on earnings persistence and market pricing: Evidence from Korea - Hee Young Ma; Ji Yeon Yoo (Journal of Business Economics and Management (JBEM), 2022)
This study examines the implications of sustainable management for the persistence of earnings and earnings components. This study also analyzes whether sustainable management influences investors' assessments of earnings persistence. According to previous studies, sustainable management activities ultimately have a positive effect on corporate financial performance and corporate value by satisfying the desires of not only shareholders, but also various actors concerned with social contributions and reduced information asymmetry. In addition, the transparency of financial reporting increases as earnings management decreases due to ethical management. So this study predicts that excellent sustainable management activities will improve earnings persistence and investors use as a signal to correctly price the persistence of earnings. This research uses the ESG ratings as a proxy for sustainable management and sample size is 3,247 in Korea securities market. The empirical results show that there is a significant positive relationship between higher ESG grades and earnings and earnings components. And by the method of Mishkin (1983), investors correctly price the persistence of earnings and earnings components based upon sustainable management activities. The results in this study helps to improve our understanding of the impact of sustainable management for earnings quality and investors' evaluation of earnings quality.
Keywords: M14; M40; 650; sustainable management; ESG; earnings persistence; earnings quality; market pricing; investment decision